Massive Governance, Miserable Populace: Cost Of Governance As Economic Growth Decelerator In Nigeria - Udoinyang, Nathan; Daniel, Reuben; Ifeoma, Grace E; Eduviere, Victoria O; Nkemdilim, Ebor R; David, Abroad E (International Ecsis Association, 2024)
This study looks at massive governance, miserable populace: cost of governance as economic growth decelerator in Nigeria. This study used surveys to collect a total of 310 respondent. Looking back, we see how cost of governance become a negative impact on Nigeria's economic growth; We see that revenue from many sectors is used to finance massive governance which slows down the growth of Nigeria, massive governance weakens the Nigerian economy and slows down the growth of Nigeria economy. The heavy debt service economy has become the basis of Nigeria's economic growth, leading to excessive and ineffective spending of Nigerian funds by the political class. The study concluded that Nigerians will experience sustainable economic growth that will lead to development if she promotes and accepts a part-time unicameral legislature which will reduce the size of the political class and the salary structure, her economy will continue to slow down, thereby causing population poverty and course diseases in the country. The study also makes some recommendations to Nigerians and policy makers. Implication of this research is that by adopting a part-time unicameral legislature to minimize governance costs.